Incidence of seizure in stroke patients treated with recombinant tissue plasminogen activator: A systematic review and meta-analysis. Issue 9 (December 2017) - Lekoubou, Alain; Awoumou, Jean Joël; Kengne, André Pascal
Background: Recombinant tissue plasminogen activator is the only FDA-approved thrombolytic agent for acute stroke treatment. However, there are concerns that recombinant tissue plasminogen activator may increase the risk of seizures (including early and late seizures). Aims: We performed a systematic review to assess the incidence of seizures and the association of recombinant tissue plasminogen activator with seizure occurrence. Summary of review: We searched major databases for articles published between 1995 and February 2016. The pooled incidence of post-stroke seizure, early seizure, late seizure, and seizures sub-types was estimated overall and by status for recombinant tissue plasminogen activator treatment, and unadjusted odds ratio used to quantify the effects of recombinant tissue plasminogen activator on post-stroke seizure occurrence. In all, 4362 stroke participants were included with 49–63% being male and median age ranging from 68 to 71 years. A total of 792 received recombinant tissue plasminogen activator. The incidence of post-stroke seizure per 1000 participants (95% CI) was 95 (31–196) overall, 113 (49–202) in recombinant tissue plasminogen activator and 169 (6–326) in non-recombinant tissue plasminogen activator-treated (all heterogeneity- p <0.0001). Incidence of early seizure per 1000 (95% CI) was 35 (27–45) overall; 34 (22–50) among recombinant tissue plasminogen activator-treated patients, and 36 (25–48) among recombinant tissue plasminogen activator naïve participants (all heterogeneity- p  > 0.826). The pool incidence rate per 1000 (95% CI) of late seizure was 84 (4–263), 46 (2–145), and 212 (184–241), respectively, in the overall, the recombinant tissue plasminogen activator-treated group and non-recombinant tissue plasminogen activator-treated group (heterogeneity for overall and recombinant tissue plasminogen activator-treated group < 0.0001, non-recombinant tissue plasminogen activator naïve = 0.999). The pooled odds ratio for post-stroke seizure (recombinant tissue plasminogen activator vs. no recombinant tissue plasminogen activator) was 0.94 (95% CI: 0. 17–5.26, heterogeneity- p  < 0.0001). The pooled incidence per 1000 participants (95% CI) was 30 (0–144), 17 (2–49), 16 (2–44), and 9 (0–50), respectively, for focal seizure without impairment of consciousness, focal seizure with impairment of consciousness, generalized convulsive seizure, and status epilepticus; all heterogeneity- p  < 0.0003. Accompanying pooled odds ratio (recombinant tissue plasminogen activator vs. no recombinant tissue plasminogen activator) based on one study was always in favor of non-significantly lower risk in recombinant tissue plasminogen activator-treated patients (all heterogeneity- p  = 1). There were insufficient data to compute pooled odds ratio for early and late seizure. Conclusions: Seizures affect nearly 1 out of every 10 stroke patients with inconclusive suggestion that rates are similar in recombinant tissue plasminogen activator-treated and recombinant tissue plasminogen activator naïve patients. Large prospective studies are needed to better understand the relationship between recombinant tissue plasminogen activator and post-stroke seizure occurrence.